Tribute to Dr. Mario Augusto Taricco - Vellutini, Eduardo de Arnaldo Silva; Pahl, Felix Hendrik; Oliveira, Matheus Fernandes de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
The present article is a brief tribute to Dr Mario Augusto Taricco, highlighting his contributions to Brazilian neurosurgery during his prestigious professional career. Dr Taricco was born in São Paulo, state of São Paulo, Brazil, and contributed to neurosurgery and spinal surgery for 42 years, leaving a vast legacy for São Paulo's and national neurosurgery. Based on values such as discipline, ethics, professionalism and competence, he built his own brand leading and improving neurosurgery and spine surgery in Brazil. He graduated in the Escola Paulista de Medicina and became neurosurgeon at the Hospital das Clínicas of the Universidade de São Paulo (FMUSP, in the Portuguese acronym). Since 1989, he became the head of the Spine Surgery Group of the Neurosurgery Service of Hospital das Clínicas, FMUSP. A career dedicated to professional and academic excellence, focused on patient treatment and science improvement.
Keywords: Mário Taricco; neurosurgery; spinal surgery; history